(untitled) (Iris Journal of Scholarship, 2019)
Food is one of the fundamental aspects of human existence. Thus, it important for every country in the world to be able to be food-secure. Providing access to food for its citizens will bring positive long-term impacts ranging from economic growth and job creation, poverty reduction, trade opportunities, increasing global security and stability, and also improving health and healthcare in a nation (National Institute of Food and Agriculture, n.d.). However, not every nation has the capacity to achieve that goal due to several contributing factors such as 1) Drought and other extreme weather events, 2) Pests, livestock diseases and other agricultural problems, 3) Climate change, 4) Military conflicts, 5) Lack of emergency plans, 6) Corruption and political instability, 7) Cash crops dependence, 8) AIDS as it reduces the available workforce in agriculture and puts an additional burden on poor households, 9) Rapid population growth. Yemen, and Burundi were intentionally chosen to be analyzed because of their unambiguous differences in order to show the various needs and solutions of each country. These 2 countries represent different rankings in the Global Food Security Index (GFSI 2018) where Burundi became the lowest ranking country, yet poses an interesting connection to Yemen. Yemen was selected because of the current famine crisis happening. From the analysis conducted, it can be concluded that long-standing conflict, Scarcity of basic needs, blockade of import and export activities are the main factors contributing to Yemen’s food insecurity. On the other hand, it was found that Gender inequality especially the role of women in labor force, climate shock, and political instability are the main factors contributing to Burundi’s food insecurity.